Peningkatan Kemampuan Berpikir Kreatif Melalui Penerapan Project Based Learning Pada Materi Pencemaran dan Daur Ulang Limbah - Gilang Akbar Nugroho; Baskoro Adi Prayitno; Joko Ariyanto (BIO-PEDAGOGI, 2017)
This study aims to improve the ability of creative thinking through Project Based Learning on pollution and waste recycling materials. This research is a classroom action research conducted for 2 cycles. Each research cycle consists of 4 stages, namely planning, action, observation, and reflection. The subjects of the study were the students of grade X SMA N 2 Boyolali with 37 students. Research data obtained through class observation, interviews, documentation, and tests of creative thinking ability that consists of aspects of fluency, flexibility, originality, and elaboration. Validation of data is done by triangulation technique. Data analysis using qualitative descriptive analysis technique. The results showed that each aspect of creative thinking ability in pre-cycle that is fluency 25,4% included in category less, flexibility 24,8% included in category less, originality 15,9% included in category less, and elaboration 18,6 % Included in the category less. The achievement percentage of each aspect of the ability of creative thinking in the first cycle that is fluency 34.5% included in the category enough, flexibility 41.8% included in the category enough, originality 37% included in the category enough, and elaboration 40.5% included in the category enough. The achievement percentage of each aspect of creative thinking ability in cycle II that is fluency 78,6% included in creative category, flexibility 52,1% included in enough category, 48,9% originality included in enough category, and elaboration 58,6% including In sufficient category. The achievement of students' creative thinking ability from pre-cycle to cycle II has increased according to the research target of ≥20% through the implementation of Project Based Learning model